A autoria no contexto acadêmico: uma questão de prosódia - Barreto, Juliana Pereira Souto (2011)
This research aims to identify, from the observation of the language used by teachers in the classroom, aspects of intonation in spoken language to justify an academic evaluative relationship between authorship and prosody. We adopt the view which the subject is constituted author of his or her spoken words once he or she is positioned, thus assuming an appreciative speech over his or her enunciation. This finding fact is passive to be outlined from the point that knowledge takes place in identifying relations established between individuals through the choice of prosodic language resources, elements which characterize the authorship construction process in the academic context. It is examined the occurrence of these prosodic elements in the construction of meaning in oral texts produced by the subject teacher in the classroom from his or her speech production, the result of rereading related to the content being discussed in class. This work is based on the concept of Authorship described by Bakhtin (1990, 2003) and on the Intonation Interactional Theory developed by David Brazil (1981, 1985). We analyzed the speeches of two teachers in their structure, communicative context, the speaker's intention, degree of hierarchy between the participants and the presence and influence of prosodic factors. We conclude that the identification of constitutive marks of the author highlights the necessity of observing the teacher's prosodic ability as speaker in dealing with language, emphasizing the practice of an oriented responsive speech, in which the assessment is an instrument that gives the speaker the power to rearrange his or her own thoughts in favor of what is stated. It is proposed, therefore, the construction of more appreciative discourses and less significant discourses to assist in targeting the intended meaning and purpose of the content covered in class, so that the individual teacher acquires the power to exercise his or her speech in an authentic manner, producing knowledge much more than merely reproducing knowledge within the academic context